Assessing the invasive potential of Saguinus midas in the extent of occurrence of the critically endangered Saguinus bicolor - Lagroteria, Diogo; Cavalcante, Thiago; Zuquim, Gabriela; Röhe, Fábio; Medeiros, Aline S. M.; Hrbek, Tomas; Gordo, Marcelo (Frontiers in Conservation Science, 2024)
Saguinus bicolor is one of the most endangered primates in the Amazon, mainly due to threats related to human activities, such as deforestation and habitat fragmentation. Moreover, the encroachment of Saguinus midas, a competing sister species, into the restricted range of S. bicolor, poses further conservation challenges and extinction risks. Evaluating the potential range expansion of S. midas towards that of the critically endangered S. bicolor is essential for science-based conservation and environmental management strategies. This study investigates the potential of invasion by S. midas into the area of occurrence of S. bicolor by quantifying and comparing the habitat suitability for both species. We use environmental variables that are known to be relevant descriptors of callitrichid niches and we also apply a similarity test to assess the niche overlap between the two species. Our analysis reveals that the majority of the area occupied by S. bicolor exhibits higher habitat suitability for S. midas than for S. bicolor. Furthermore, we found a high niche similarity between the species. These results suggest high invasive potential of S. midas into the range of S. bicolor. Notably, our findings also indicate that S. midas is a more generalist species, implying a competitive advantage over S. bicolor. The long-term persistence prospects of S. bicolor are worrisome, thus we propose strategies for the conservation of the species. The conservation and maintenance of an ecologically functional urban forest matrix, which can act as a refuge for S. bicolor, as well as the maintenance of habitat quality and connectivity in rural areas, are crucial. Monitoring the current contact areas between the two species and the areas indicated as of high and medium habitat suitability for S. midas in the range of S. bicolor is also very important, and the observed trends in the occupation of these areas need to be incorporated into adaptive conservation strategies of these less anthropogenically impacted areas.